Assisted Reproduction and Distributive Justice. (8th November 2013) - Panitch, Vida
Abstract The Canadian province of Quebec recently amended its Health Insurance Act to cover the costs of In Vitro Fertilization (IVF). The province of Ontario recently de‐insured IVF. Both provinces cited cost‐effectiveness as their grounds, but the question as to whether a public health insurance system ought to cover IVF raises the deeper question of how we should understand reproduction at the social level, and whether its costs should be a matter of individual or collective responsibility. In this article I examine three strategies for justifying collective provisions in a liberal society and assess whether public reproductive assistance can be defended on any of these accounts. I begin by considering, and rejecting, rights‐based and needs‐based approaches. I go on to argue that instead we ought to address assisted reproduction from the perspective of the contractarian insurance‐based model for public health coverage, according to which we select items for inclusion based on their unpredictability in nature and cost. I argue that infertility qualifies as an unpredictable incident against which rational agents would choose to insure under ideal conditions and that assisted reproduction is thereby a matter of collective responsibility, but only in cases of medical necessity or inability to pay. The policy I endorse by appeal to this approach is a means‐tested system of coverage resembling neither Ontario nor Quebec's, and I conclude that it constitutes a promising alternative worthy of serious consideration by bioethicists, political philosophers, and policy‐makers alike.